Perancangan Game Edukasi Aksara Jawa Untuk Siswa Kelas V SDIP Haji Muhammad Subandi Kecamatan Bawen - Ridlo Qoirul Anhari; Agus Priyadi; Ahmad Zainudin (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The rapid advancement of digital technology has significantly influenced students’ learning behavior while gradually reducing their interest in local cultural education, including the study of the Javanese script. This phenomenon is evident at SDIP Haji Muhammad Subandi, where most students still struggle to recognize, read, and understand Javanese characters due to the limited use of engaging and interactive learning media. To address this issue, a 2D educational game was developed as an innovative, contextual, and enjoyable learning medium that integrates cultural elements into an interactive digital learning experience. The design and development process employed the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The game was built using Unity software to produce dynamic visuals, responsive controls, and supporting audio elements that enhance the immersive quality of gameplay. The educational game enables students to learn Javanese script through interactive play activities, including letter recognition, pronunciation practice, and quiz-based challenges. Each component was designed to strengthen cognitive understanding while increasing students’ intrinsic motivation to learn. Expert validation results indicated that the game met the “highly feasible” criteria as a learning medium, while user testing showed notable improvements in motivation, engagement, and learning enjoyment. Overall, this educational game not only enhances learning effectiveness but also contributes to the preservation and revitalization of the Javanese script as part of Indonesia’s cultural heritage in the digital era. Therefore, this game-based learning approach serves as an adaptive and culturally grounded educational innovation for primary-level students